Predicting VR acceptance based on race, gender, education, work status at application, and primary source of support at application. - Wilson KB; Alston RJ; Harley DA; Mitchell NA (Rehabilitation Counseling Bulletin, 2002)
The relationship between vocational rehabilitation (VR) acceptance and race, gender, education, work status at application, and primary source of support at application was examined using a binary logistic regression. Based on the use of a stepwise entry method, race, primary source of support at application, and education were found to be statistically significant. Moreover, after all variables were entered into the binary logistic regression equation, the total amount of variance explained in the dependent variable by the independent variables was 5.3%. Compared to European Americans, African Americans were 2.12 times more likely to be accepted for VR services, when controlling for all other variables in the study. Compared to customers who reported only their own income at application, individuals who reported income from family and friends and other sources were negatively associated with VR acceptance, after controlling for all other variables in the study. Implications for VR counselors are discussed.